2023
DOI: 10.1186/s40537-022-00680-6
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning-based model using hybrid feature extraction approach for consumer sentiment analysis

Abstract: There is an exponential growth in textual content generation every day in today's world. In-app messaging such as Telegram and WhatsApp, social media websites such as Instagram and Facebook, e-commerce websites like Amazon, Google searches, news publishing websites, and a variety of additional sources are the possible suppliers. Every instant, all these sources produce massive amounts of text data. The interpretation of such data can help business owners analyze the social outlook of their product, brand, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…Also, he found that simpler models such as LR and SVM were more effective at predicting sentiments than more complex models like Gradient Boosting, LSTM, and BERT. G. Kaur1 et al, 2023 [24] introduce a method for sentiment analysis that combines different approaches. The process involves three main steps: pre-processing, feature extraction, and sentiment classification.…”
Section: Related Workmentioning
confidence: 99%
“…Also, he found that simpler models such as LR and SVM were more effective at predicting sentiments than more complex models like Gradient Boosting, LSTM, and BERT. G. Kaur1 et al, 2023 [24] introduce a method for sentiment analysis that combines different approaches. The process involves three main steps: pre-processing, feature extraction, and sentiment classification.…”
Section: Related Workmentioning
confidence: 99%
“…In [2], research work focuses on developing a consumer review summarization model that uses Natural Language Processing (NLP) techniques and Long short-term memory (LSTM) to provide concise and meaningful data, enabling businesses to gain valuable insights into their customers' behavior and preferences. The authors have presented a hybrid approach for sentiment analysis.…”
Section: Detailed Literaturementioning
confidence: 99%
“…In [2], a customer's review summarization model is developed using natural language processing techniques and deep learning model that is LSTM. The process consists of pre-processing, feature extraction, and sentiment classification.…”
Section: Critical Analysismentioning
confidence: 99%
“…NLP plays an important role in ABSA for restaurant reviews, employing advanced machine learning and linguistic algorithms to break down complex, unstructured textual data into meaningful components [8]. This method enables the extraction of specific aspects such as food quality, service, ambiance, and others, providing a comprehensive understanding of customer sentiments [9].…”
Section: Introductionmentioning
confidence: 99%